Nauki rolnicze a wielofunkcyjny i zrównoważony rozwój rolnictwa - Adamowicz, Mieczysław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2004)
The aim of the paper is discussing the multifunctionality of agriculture and its links with sustainable development as well as the role of agricultural sciences in implementation of those ideas. The industrialization and modernisation of agriculture and their limitations were presented on the ground of general description of development rules. The idea of multifunctionality and its forms, multifunctional dimension of agricultural farms, multifunctional strategies and their effects were analysed. Proposals for the role of agricultural sciences in multifunctional and sustainable development of agriculture in Poland were suggested.